Prevalence of Microalbuminuria with Relation to Glycemic Control in Type-2 Diabetic Patients in Mymensingh - Hasan, Mahmud Javed; Islam, Nazrul; Sharmeen, Atia; Kabir, ATM Sulaiman; Bari, Muhammad Abdul; Ahmed, Sultan; Haque, Amdadul (Community Based Medical Journal, 2014)
Diabetes is one of the most common endocrine disorders characterized by hyperglycaemia. Diabetic nephropathy is a consequence of long standing diabetes. The prevalence of microalbuminuria predicts progression to diabetic nephropathy. The present study was conducted to determine the prevalence of microalbuminuria in relation to duration of diabetes, BMI, Serum Creatinine and HbA1c in an ethnic group of Type 2 diabetes mellitus residing in Mymensingh, Bangladesh. This descriptive cross-sectional study was carried out in a community based medical college hospital, located at Winnerpar, Mymensingh from July to December 2012. Fasting various blood and morning urine sample was collected for analysis of creatinine, HbA1c and microalbuminuria respectively. One hundred twenty known Type 2 diabetic patients with age 30 years and above were included in the study. Pearson correlation was applied to observe association of microalbuminuria with different parameters. Microalbuminuria had a highly significant correlation with duration of diabetes (p<0.001), serum creatinine, HbA1c (p<0.001) and BMI (p 0.001). The correlation demonstrates that with the increase in age, raised serum creatinine significantly bearing a perfect positive correlation as evident by r = 0.878, p < 0.001. The present study found an early onset of microalbuminuria in the selected community which could be due to poor glycaemic control (high HbA1c >7%) or heredity factors. Screening for microalbuminuria and HbA1c test should be done in both newly and already diagnosed Type 2 diabetic patients as an early marker of renal dysfunction and glycaemic control. CBMJ 2014 January: Vol. 03 No. 01 P: 29-34